QUALITY OF LIFE COMPARATION IN METASTATIC BONE DISEASE PATIENT BEFORE AND AFTER SURGERY IN DR. SOETOMO GENERAL HOSPITAL - Ferdiansyah Mahyudin; Mouli Edward; Muhammad Hardian Basuki; Rizky Agung Satria (Universitas Airlangga, 2018)
Background: Metastatic bone disease is bone pathologic process caused by spread of primary tumor. The incidence of metastatic bone disease varies between 20-75% corresponds to the primary site of the malignancy. Surgery in metastatic bone disease aim to cure or palliate the morbidity caused by the disease. Operative treatment could reduce pain, improve function, control metastatic focus of the malignancy, and provide mechanical stabilization. Based on those benefits, operative treatment is important to improve quality of life in patients with metastatic bone disease. Purpose: Proved that there was a difference in the quality of life MBD patients before and after surgery.Methods: This research was a retrospective cohort on MBD patients which undergone surgery, and never given any other treatment in the course of the disease. The research was conducted in Dr. Soetomo General Hospital, Surabaya. Patient sampling was done using consecutive sampling. Karnofsky score was taken from the medical record before the procedure and direct interview via phone or completing questionnaire. Data analysis was done descriptively and analytically. Statistical tests were done using Wilcoxon test.Results: 146 patients enrolled in the research. The mean age of the sample was 48.77 ± 13.34 years. The mean of Karnofsky score before and after the procedure was 53.69±13.07 and 75.54±13.69 with statistical result of p<0.001.Conclusion: The Karnofsky score in MBD patients was higher after the surgery compared to before the surgery.